Two Escherichia coli chromosomal cistrons, sfrA and sfrB, which are needed for expression of F factor tra functions. - Beutin, L (1979)
Twelve mutants of Escherichia coli K-12 have been isolated which carry chromosomal mutations that exhibit pleiotropic effects on the expression of F factor tra cistrons. F pilus synthesis, deoxyribonucleic acid transfer, and surface exclusion are all inhibited. Six of the mutants carry sfrA mutations, and six carry sfrB mutations. sfrA and sfrB are cistrons mapping near thr and metE, respectively. Several F-like plasmids are dependent on sfrA and on sfrB for expression of tra cistrons. Plasmids of incompatibility groups C and S are only dependent on sfrB,and other conjugative plasmids are dependent on neither. sfrB mutations also result in changes in certain cell envelope properties, including change sensitivity to certain bacteriophages which use lipopolysaccharide as a receptor, synthesis of nonfunctional flagella, and altered sensitivity to antibiotics.